Securing quick response (QR) code using steganography / Muhammad Danial Mohd Alwi - Mohd Alwi, Muhammad Danial (2021)
Quick Response (QR) codes are two-dimensional standardized tags that can be utilized to store little amounts of information effectively. In all fields of life, they are increasingly used, particularly with the large distribution of smart phones used as QR code scanners. While there are several benefits to QR codes that make them very common, there are many security problems and risks associated with them. Running malicious code, stealing sensitive information from users, and violating their privacy and identity theft are some typical security risks that a user might face in the background while just reading the QR code in the foreground. This paper implements a security system for QR codes that guarantees security concerns for both users and generators. In this work, Steganography is implemented in images with a view to improving both images' security and quality. The algorithm used here is LSB (Least Significant Bit). This is one of the most effective ways to hide the message. It allows transfer of messages from one place to another in a secure way. However, retrieval of hiding messages has become possible to the third person in the modern age. The message is stored in the image based on the message storage block. A major issue is the possibility of another person obtaining stored messages as previous methods partially hid them. I have enhancing the QR-code steganography method by using LSB technique in RGB images and QR-code data input image pattern. An LSB method is presented in this paper to hide the message clearly within the secure transfer.